Preventing Sexual Violence in Adolescence: Comparison of a Scientist-Practitioner Program and a Practitioner Program Using a Cluster-Randomized Design - Muck, Christoph (Journal of interpersonal violence, 2021)
Numerous school-based prevention programs have been developed by scientists and practitioners to address sexual violence in adolescence. However, such programs struggle with two major challenges. First, the effectiveness of many well-established practitioner programs has not been rigorously evaluated. Second, effective scientific programs may be hard to implement into everyday school practice. Combining the knowledge of scientists and practitioners in a scientist-practitioner program could be a helpful compromise. The aim of the present study is to evaluate the effects of a scientist-practitioner program and a practitioner program using a cluster-randomized experimental design. Twenty-seven school classes were randomly assigned to either one of two programs or a control group. Outcome variables (knowledge, attitudes, behavior, and iatrogenic effects) were assessed at pretest, posttest, and a 6-month follow-up for 453 adolescents (55% female, Mage = 14.18). Short-term effects were found in both programs regarding general knowledge, knowledge of professional help, and victim-blaming attitudes. Long-term effects were found in both programs regarding general knowledge and knowledge of professional help and, in the practitioner program, in a reduction of victimization. No other effects were found on attitudes and behavior. No iatrogenic effects in the form of increased anxiety were found. Both the scientist-practitioner and the practitioner program show promise for the prevention of sexual violence in adolescence; in particular, the practitioner program may be a more cost-effective method.